2014
DOI: 10.1136/bmj.g5651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a patient oriented decision aid for prioritising treatment goals in diabetes: pragmatic randomised controlled trial

Abstract: Objective To assess the effects of a patient oriented decision aid for prioritising treatment goals in diabetes compared with usual care on patient empowerment and treatment decisions. Design Pragmatic randomised controlled trial.Setting 18 general practices in the north of the Netherlands.Participants 344 patients with type 2 diabetes aged ≤65 years at the time of diagnosis and managed in primary care between April 2011 and August 2012: 225 were allocated to the intervention group and 119 to the usual care gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 42 publications
(23 reference statements)
2
77
1
2
Order By: Relevance
“…We expected some variation amongst patients, as the incomplete utilization of decision aids by patients has been previously reported and may relate to the salience of materials to the individual patient. 43,44 Another uncertainty is the effect of the design of the decision/choice set in the PtDAs. The choice architecture of the LONG and SHORT DA directed the patient to consider 5 choices: take no treatment, continue current treatment, begin Enbrel now, ask doctor about other options, and defer choice for now.…”
Section: Discussionmentioning
confidence: 99%
“…We expected some variation amongst patients, as the incomplete utilization of decision aids by patients has been previously reported and may relate to the salience of materials to the individual patient. 43,44 Another uncertainty is the effect of the design of the decision/choice set in the PtDAs. The choice architecture of the LONG and SHORT DA directed the patient to consider 5 choices: take no treatment, continue current treatment, begin Enbrel now, ask doctor about other options, and defer choice for now.…”
Section: Discussionmentioning
confidence: 99%
“…83 A randomized controlled trial evaluated whether assessment of barriers to self care and strategies to cope with these barriers, implemented telephonically by a diabetes educator, was superior to usual care with control for attention time. 76 The intervention group received a model of care in which a geriatric diabetes team assessed barriers and developed strategies to help patients to cope with barriers.…”
Section: Care Managementmentioning
confidence: 99%
“…For example, in a group of 344 patients with type 2 diabetes, intervention was introduced to assist the patients in their decision-making ability, as well as to provide individually tailored training and more treatment options [34]. After the intervention, there was no statistically significant increase in the empowerment score (determined using a structured questionnaire) and no change in the lipid profile compared to the control group [34].…”
Section: The Effects Of Empowerment Therapy In Type 2 Diabetes Andmentioning
confidence: 99%
“…For example, in a group of 344 patients with type 2 diabetes, intervention was introduced to assist the patients in their decision-making ability, as well as to provide individually tailored training and more treatment options [34]. After the intervention, there was no statistically significant increase in the empowerment score (determined using a structured questionnaire) and no change in the lipid profile compared to the control group [34]. In another study (the Peer-Led, Empowerment-Based Approach to Self-Management Efforts in Diabetes, or PLEASED study), no improvement in metabolic control in patients with type 2 diabetes was observed after one year of the intervention compared to the diabetes self-management education (DSME) control group [35].…”
Section: The Effects Of Empowerment Therapy In Type 2 Diabetes Andmentioning
confidence: 99%